Discovery and Analysis of Key Core Technology Topics in Proton Exchange Membrane Fuel Cells Through the BERTopic Model - Yurong Gou; Qimei Chen (Energies)
As a core component of clean energy technology, proton exchange membrane fuel cells (PEMFC) play a crucial role in promoting the evolution of energy structures and realizing sustainable development, representing an environmentally friendly energy conversion strategy. This paper identifies the key core technology themes in the field of the proton exchange membrane fuel cells by constructing patent and paper datasets in the field, applying the BERTopic model for theme identification, and calculating the key core technology scores of each theme using the importance, innovativeness, and high competitiveness barriers to identify the key core technology themes in the field, so as to provide guidance and references for the relevant research and practice. The results of the study show that patent documents and academic papers show obvious differentiation in technical themes: the key core technologies identified in patent texts include ‘battery separator materials’, ‘rubber sealing materials’, and ‘porous carbon fibre materials’. The key core technologies identified in the academic paper of the thesis include ‘palladium-based electrocatalys’, ‘graphene oxide composite film’, and ‘platinum-graphene oxide catalyst’.